BANKS AND BANKING BUSINESS IN RUSSIA IN THE FACE OF INTERNATIONAL SANCTIONS - G. S. Panova (Vestnik MGIMO-Universiteta, 2016)
The article provides an analysis of the present condition and prospects of development of banks and the banking business in the face of international sanctions. It identifies current trends, problems and the risks of banks and banking in Russia and in the world. Special attention is paid to the analysis of sectoral international sanctions against the Russian banks and the need to minimize negative impact of sanctions on the banking business, both nationally and internationally. Great value in these conditions has the state monetary policy. Anti-crisis policy pursued by the Bank of Russia, in a context of stagnating economy, leads to a reduction in the Russian share in the world economy and increases in the standard of living gap with the developed countries. The article argues that Russia's economic growth opportunities in 2016 are limited by restriction level of bank interest, the high volatility of the exchange rate of the national currency, insufficient development of credit relations, tough, high-budget (at the level of developed Europe) tax burden, increasing administrative costs, dramatically increasing the concentration of risks of subjective decisions at the present stage of the electoral cycle. In a situation of uncertainty of predictions regarding the scope and duration of the application of sanctions, the Russian Government and the Central Bank of the Russian Federation had rightly seek to use a combination of anti-sanctions measures of austerity measures on introduction of contra-sanctions to create more comfortable conditions for doing business in Russia and her allies from member countries of Eurasian Economic Union, SCO, BRICS. The article examines the strategic aspects of development banks and banking business in Russia under the new circumstances. Given the practical recommendations on improvement of the development strategy of banks in Russia. The necessity to improve the theoretical, conceptual, methodological, her reasoning and extend the range of retrospective and prospective analysis of the State of the banking sector development strategy of the Russian economy.